A Study to Understand Parents' Perceptions and Societal Attitudes on Bharat Biotech’s Covaxin for Children - Ishu Sharma; Akanksha Nadkarni; Sonali Kudale; Shubham Shetye; Rajesh Kumar Nair; Modhi Aljuaid; Majdi Quttainah; Liem Gai Sin (AIBPM Publisher, 2022)
The recent COVID-19 pandemic has reshaped the perceptions of vaccines worldwide. Presently, vaccines are the most efficacious resource that holds the strength to reduce the risk of the disease. In contrast, public health authorities are concerned about vaccine apprehension among the general public. The distribution and consumption of these vaccines began by segregating the age groups. The eligibility of Covaxin vaccines manufactured by Bharat Biotech for children over 12 years of age makes it critical to investigate its credibility among the parents and public views regarding children receiving these vaccines. Moreover, limited information on public acceptability and trustable opinions contribute to vaccine hesitancy among parents. Consequently, the major deciding factors are getting accurate data about the Covaxinâ€™s clinical trial by Bharat Biotech, the persistence and nature of the child's immune response, and reassurance from society. This research study aims to learn more about parents' perspectives and societal attitudes towards immunity building in children by the Covaxin vaccines. The methodology adopted here leads to a precise understanding if there is any ambiguity or acceptance towards Covaxin for children in the minds of the general public.Â KeywordsBharat Biotech, Children, Clinical Trial, Covaxin, COVID-19, Immunity, Perception.